Chemical constituents from the rhizomes of Gastrodia elata f. glauca and their potential neuroprotective effects. (April 2018) - Wang, Zhi-Wei; Li, Yun; Liu, Da-Hui; Mu, Yan; Dong, Hong-Jing; Zhou, Hong-Lei; Wang, Xiao
Graphical abstract: Highlights: Three new parishin derivatives containing a trans -cinnamoyl unit and one new adenosine derivative were isolated from Gastrodia elata f. glauca. The isolated compounds were evaluated for their neuroprotective effects against 6-hydroxydopamine-induced cell death. N 6 -bis(4-Hydroxybenzyl) adenosine exhibited potent activity with an EC50 value of 12.0 μM. Abstract: A phytochemical study on the rhizomes of Gastrodia elata f. glauca resulted in the isolation of three new parishin derivatives and one new adenosine derivative, together with six known compounds. Their structures were elucidated mainly by spectroscopic analysis and compared to published data. All these isolates were evaluated for their neuroprotective effects against 6-hydroxydopamine-induced cell death, and new compound4 showed potent activity with an EC50 value of 12.0 μM.